Writing guidelines for social science students - Emerson, Lisa. (Palmmerston North; Cengege Learning, 2005)
Guide to researching, writing and presenting research reports and essays, presenting seminars and exam skills.
New Zealand editor.
Previous ed.: Palmerston North, N.Z. : Dunmore Press, 1997.
Keywords: Report writing; Study skills